An overview on non-Apis bees vis-à-vis the exploration of integrated taxonomic approach (Hymenoptera: Apoidea) - FALSWAL, Jyoti; DEY, Debjani; KUMAR, Sarita (Fragmenta entomologica, 2022)
Easy and proficient identification of species or organisms is important for various users, such as conservationists, physiologists and ecologists, etc. Taxonomy is a significant branch of biological sciences to classify the different species and understand their relationships. Currently, taxonomy’s existence is under crisis and its future protection is required in coming times. Majority of taxonomists are using phylogenetic approach for classifying different species. However, scientists believe that taxonomy should be integrative based on a comprehensive framework for delimiting and describing taxa through integrated information using various data and methodologies. This novel approach does not aim to replace the traditional taxonomy but stresses upon the delineation of species over naming new species. Integrative taxonomy defines the units of species diversity employing multiple approaches; like population genetics, phylogeography, ecology, comparative morphology, development and behaviour, etc. Disagreements among disciplines over the number and demarcation of species can be resolved by using molecular data explaining the evolutionary relationships among species. We present a comprehensive review to explore and identify various non-Apis bees and their relationships using integrated taxonomical approaches. We believe that the phylogenies and supportive data can collectively provide a comparative framework for understanding the evolutionary relationships among bee families.